Safety and efficacy of the feed additive 4‐methyl‐5‐vinylthiazole [15.018] belonging to chemical group 29 for all animal species (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; Alena Pechová; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of 4‐methyl‐5‐vinylthiazole [15.018] belonging to chemical group 29 (thiazoles, thiophene and thiazoline), when used as sensory additive (flavourings) in feed for all animal species. The FEEDAP Panel concluded that 4‐methyl‐5‐vinylthiazole [15.018] was safe at the maximum proposed use level of 0.5 mg/kg complete feed for veal calves (milk replacer), dogs, salmonids and ornamental fish. For the other species, the calculated safe concentrations in complete feed are: 0.4 mg/kg for cattle for fattening, sheep/goat, horses and cats; 0.3 mg/kg for sows and dairy cows; 0.2 mg/kg for piglets, pigs for fattening, rabbits and laying hens; and 0.1 mg/kg for chickens for fattening and turkeys for fattening. These conclusions were extrapolated to other physiologically related species. For any other species, the additive was considered safe at 0.1 mg/kg complete feed. No safety concern would arise for the consumer from the use the additive up to the maximum proposed use level in feed. The additive should be considered as irritant to skin and eyes and the respiratory tract, and as dermal and respiratory sensitisers. The use of 4‐methyl‐5‐vinylthiazole [15.018] as a flavour in animal feed was not expected to pose a risk to the environment. Since the compound under assessment is used in food as flavouring and its function in feed is essentially the same as that in food, no further demonstration of efficacy was considered necessary.